Reconstruction of Customary Law in Development Agrarian Law in the Field of Mortgage Rights - Kamilah, Anita; Dwi Astuti, Hesti; E. Tambun, Grace; Permana, Ajeng (Hukum dan Masyarakat Madani, 2025)
Customary law as one of the sources of Indonesian national law that is local and traditional, has a great influence in the development of agrarian law, and has relevance in overcoming the problems faced by the Indonesian people in the era of globalization. This research has an important role in examining issues regarding: (1) Customary law as the basis of Indonesian national agrarian law; and (2) Reconstruction of customary law in Indonesian national agrarian law in the field of mortgage rights. The method used in this research, through a doctrinal legal research approach, descriptive analysis research specifications, types and sources of data come from secondary data sourced from primary legal materials, secondary legal materials, and tertiary legal materials, and data analysis is carried out qualitatively. The results of the study; (1) The enactment of Law No. 5 of 1960 concerning Basic Regulations on Agrarian Principles is not based on western colonial agrarian law, but is based on customary law as a manifestation of Indonesian legal politics to eliminate dualism in agrarian law; and (2) Reconstruction of customary law institutions in the land sector is carried out by incorporating the concepts and principles of customary law into new legal institutions, including land mortgages, which are a source of inspiration for the formation of national law.